Direct activation of tachykinin receptors within baroreflex afferent pathway and neurocontrol of blood pressure regulation. (13th June 2018) - Yuan, Mei; Ma, Mei‐Na; Wang, Ting‐Yu; Feng, Yan; Chen, Pei; He, Chao; Liu, Sijie; Guo, Yun‐Xia; Wang, Yue; Fan, Yao; Wang, Lu‐Qi; E, Xiao‐Qiang; et al.
Summary: Aim: Substance P (SP) causes vasodilation and blood pressure (BP) reduction. However, the involvement of tachykinin receptors (NKRs) within baroreflex afferent pathway in SP‐mediated BP regulation is largely unknown. Methods: Under control and hypertensive condition, NKRs' expressions were evaluated in nodose (NG) and nucleus of tractus solitary (NTS) of male, female, and ovariectomized (OVX) rats; BP was recorded after microinjection of SP and NKRs agonists into NG; Baroreceptor sensitivity (BRS) was tested as well. Results: Immunostaining and immunoblotting data showed that NK1R and NK2R were estrogen‐dependently expressed on myelinated and unmyelinated afferents in NG. A functional study showed that BP was reduced dose‐dependently by SP microinjection, which was more dramatic in males and can be mimicked by NK1R and NK2R agonists. Notably, further BP elevation and BRS dysfunction were confirmed in desoxycorticosterone acetate (DOCA)‐salt model in OVX compared with DOCA‐salt model in intact female rats. Additionally, similar changes in NKRs' expression in NG were also detected using DOCA‐salt and SHR. Compared with NG, inversed expression profiles of NKRs were also found in NTS with either gender. Conclusion: The estrogen‐dependent NKRs' expression in baroreflex afferent pathway participates at least partially in sexual‐dimorphic and SP‐mediated BP regulation under physiological and hypertensive conditions.